Intracellular polyamines mediate inward rectification of Ca(2+)-permeable alpha-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid receptors. - Donevan, S D (1995)
alpha-Amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) receptors that lack the glutamate receptor GluR2 subunit are Ca(2+)-permeable and exhibit inwardly rectifying current responses to kainate and AMPA. A proportion of cultured rat hippocampal neurons show similar Ca(2+)-permeable inwardly rectifying AMPA receptor currents. Inward rectification in these neurons was lost with intracellular dialysis and was not present in excised outside-out patches but was maintained in perforated-patch whole-cell recordings, suggesting that a diffusible cytoplasmic factor may be responsible for rectification. Inclusion of the naturally occurring polyamines spermine and spermidine in the recording pipette prevented loss of rectification in both whole-cell and excised-patch recordings; Mg2+ and putrescine were without effect. Inward rectification of Ca(2+)-permeable AMPA receptors may reflect voltage-dependent channel block by intracellular polyamines.